2018
DOI: 10.18689/ijmr-1000101
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 Deficiency Leads to a Dysregulation in the Global Gene-Expression Profile in Murine Oviduct Epithelial Cells Infected with Chlamydia muridarum

Abstract: Chlamydia trachomatis replicates primarily in the epithelial cells lining the genital tract and induces the innate immune response by triggering cellular pathogen recognition receptors (PRRs). Our previous studies showed that Toll-like receptor 3 (TLR3) is expressed in murine oviduct epithelial (OE) cells, is the primary PRR triggered by C. muridarum (Cm) early during infection to induce IFN-β synthesis, and that TLR3 signaling regulates the chlamydial induced synthesis of a plethora of other innate inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Based on the role in transcriptional and translational interference, MX1 and MX2 upregulation by pOECs could aim to limit Ct propagation and thereby Ct infection within the genital tract. Regarding CMPK2, studies using murine genital tract epithelial cells have also shown an upregulation of CMPK2 mRNA upon C. muridarum infection [60]. The enzyme CMPK2 not only supplies deoxyribonucleotides for the synthesis of mitochondrial DNA (mtDNA) [61] but it also possesses immunomodulatory and antiviral activities: CMPK2 was shown to limit dengue virus infection of murine and human cells in an IFN-dependent and IFN-independent manner [62].…”
Section: Innate Immune Response Of Porcine Oviduct Epithelial Cells To Chlamydia Trachomatis Infectionmentioning
confidence: 99%
“…Based on the role in transcriptional and translational interference, MX1 and MX2 upregulation by pOECs could aim to limit Ct propagation and thereby Ct infection within the genital tract. Regarding CMPK2, studies using murine genital tract epithelial cells have also shown an upregulation of CMPK2 mRNA upon C. muridarum infection [60]. The enzyme CMPK2 not only supplies deoxyribonucleotides for the synthesis of mitochondrial DNA (mtDNA) [61] but it also possesses immunomodulatory and antiviral activities: CMPK2 was shown to limit dengue virus infection of murine and human cells in an IFN-dependent and IFN-independent manner [62].…”
Section: Innate Immune Response Of Porcine Oviduct Epithelial Cells To Chlamydia Trachomatis Infectionmentioning
confidence: 99%
“…It is well known that C. trachomatis infects mainly the epithelial cells of the genital tract, but it can also replicate into different cell types, including synovial cells, human placental trophoblasts, and testicular human Sertoli cells [5][6][7][8][9][10]. Following chlamydial infection, the host cell response begins with the activation of a complex network of immune receptors and their unique downstream signaling pathways, resulting in the induction of proinflammatory cytokines involved in either the elimination of C. trachomatis or tissue damage related to chronic inflammatory state.…”
Section: Introductionmentioning
confidence: 99%
“…Following chlamydial infection, the host cell response begins with the activation of a complex network of immune receptors and their unique downstream signaling pathways, resulting in the induction of proinflammatory cytokines involved in either the elimination of C. trachomatis or tissue damage related to chronic inflammatory state. In particular, Toll-like receptors (TLRs), TLR2, TLR3 and TLR4, and oligomerization domain (NOD)-like receptors (NLRs), NOD1, as well as the respective downstream signaling pathways, like NFκb, IRF9 and MyD88, have been identified in the immune recognition of C. trachomatis in several in vivo and in vitro models [5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%